Rehabilitation Impact of Vivifrail Exercise Program Type C on the Cognitive Function of Pre-Frail Elderly People in the Community - Sri Soenarti; Dwi Indriani Lestari; Muhammad Barlian Nugroho; Harien Lestari; Tita Hariyanti (Folia Medica Indonesiana)
Highlights: 1. This study emphasizes the importance of providing physical exercises to pre-frail elderly individuals, especially in a community setting. 2. This study establishes a foundation for future research to explore the relationship between physical exercise, particularly the Vivifrail Type C Protocol, and cognitive function in pre-frail elderly individuals.